2017
DOI: 10.1016/j.jfma.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane targets cancer stemness and tumor initiating properties in oral squamous cell carcinomas via miR-200c induction

Abstract: These lines of evidence suggest that sulforaphane can suppress the cancer stemness and tumor-initiating properties in OSCC-CSCs both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 39 publications
5
28
1
Order By: Relevance
“…Similar results with this ITC had already been reported in a panel of human primary CRC cell lines, in which impairment of anchorage-independent cell growth in vitro was also dose-dependent, and confirmed in vivo [21]. Besides, the effect of SFN in self-renewal, metastatic and tumor initiation skills in oral squamous cell carcinoma and pancreatic cancer stem-like cells were also already reported in vitro and in vivo [26,27]. …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results with this ITC had already been reported in a panel of human primary CRC cell lines, in which impairment of anchorage-independent cell growth in vitro was also dose-dependent, and confirmed in vivo [21]. Besides, the effect of SFN in self-renewal, metastatic and tumor initiation skills in oral squamous cell carcinoma and pancreatic cancer stem-like cells were also already reported in vitro and in vivo [26,27]. …”
Section: Resultssupporting
confidence: 87%
“…Despite the cumulative evidences on SFN effect in ALDH1 activity of cancer stem-like cells of other solid tumors [26,27,28,29], in our experiments the effect of this ITC, either directly or indirectly through the extract, was not verified in the context of HT29 spheroids enriched in stem-like cells. As shown in Figure 5A, in the doses tested, broccoli extract and SFN did not demonstrated potential to impair ALDH1 activity and to target ALDH + cells.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Therefore, it is necessary to identify and employ novel biomarkers as possible therapeutic targets or prognostic predictors, which will be used as an adjunct to the staging system and contribute to the optimization of treatment for patients with NSCLC. miRNAs as a recent focus in tumor research serve an oncogenic or tumor-suppressive role in different cancer types via various pathways (17)(18)(19). miR-200c is a member of the miR-200 family, which is located on chromosome 12p13 and is closely associated with carcinogenesis and disease progression in a wide range of cancer types (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have revealed that miRNAs play an important physiological and pathological role in cancers; thus, therapies targeting miRNAs may be an effective strategy to block cancer oncogenesis and progression. Several miRNAs have previously been shown to be regulated by sulforaphane [8][9][10] . Sulforaphane can modify the activity of miR-200c/ ZEB1 and the snail pathway to affect epithelial-mesenchymal transition (EMT) [11] , suggesting that sulforaphane may target specific miRNAs to promote its anti-metastatic effects in cancers.…”
Section: Introductionmentioning
confidence: 99%